2018
DOI: 10.1111/efp.12422
|View full text |Cite
|
Sign up to set email alerts
|

Infection without wounding and symptomless shoot colonization of Pinus radiata by Fusarium circinatum, the cause of pitch canker

Abstract: Summary Fusarium circinatum is widely regarded as a necrotrophic pathogen of pines that infects shoot tissue through mechanical or insect‐mediated wounds, causing girdling lesions that result in death of infected branches. However, in the study reported here, F. circinatum colonized 100% of seedling stems and 70% of mature tree branches that were not wounded. Hyphae were observed beneath the epidermis of non‐wounded shoot tissue within 14 days following inoculation. In both seedlings and branches, most infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Both P. nigra and P. sylvestris have been found to be potential hosts of F. circinatum, showing moderate susceptibility to the disease . However, the apparent absence of the pathogen in sampled mycobiota did not rule out its possible latent presence in the asymptomatic area, as recently reported in P. pinaster and P. radiata stands (Hernández-Escribano et al, 2018a;Swett et al, 2018). The results showed here are consistent with those provided by regarding T. piniperda, whereas the association between the pathogen and T.…”
Section: Conflict Of Interestsupporting
confidence: 81%
See 1 more Smart Citation
“…Both P. nigra and P. sylvestris have been found to be potential hosts of F. circinatum, showing moderate susceptibility to the disease . However, the apparent absence of the pathogen in sampled mycobiota did not rule out its possible latent presence in the asymptomatic area, as recently reported in P. pinaster and P. radiata stands (Hernández-Escribano et al, 2018a;Swett et al, 2018). The results showed here are consistent with those provided by regarding T. piniperda, whereas the association between the pathogen and T.…”
Section: Conflict Of Interestsupporting
confidence: 81%
“…mycelial strands, runner hyphae and hyphopodia-like structures, among others), while only the finest branches and roots were severely damaged. Recent studies also showed that the fungus can remain in a latent state in asymptomatic pines (Hernández-Escribano et al, 2018a;Swett et al, 2018). Consequently, the relationship between the PPC fungus and the pine host could be mainly biotrophic (i.e.…”
Section: The Pathosystem: a Network Of Interactionsmentioning
confidence: 99%
“…and F. commune (Skovgaard, O'Donnell and Nirenberg) caused damping-off in Douglas fir seedlings under greenhouse conditions. Similar results point to F. circinatum (Nirenberg and O'Donnell) as the causal agent of damping-off in seedlings of P. maximinoi (Moore) and P. tecunumanii (Maphosa et al, 2016;Martínez-Álvarez et al, 2016;García Díaz et al, 2017;Flores-Pacheco, 2017;Swett et al, 2018).…”
Section: Introductionmentioning
confidence: 61%
“…Natural infections presumably occur through wounds of the potential host, although Swett et al (2018) demonstrated that F. circinatum is also able to colonise the seedling stem and mature tree branches without wounds. Once the conidia germinate on host tissue, the fungus first moves radially through the plant, advancing towards the pith of the stem (Martín-Rodrigues et al, 2013).…”
Section: Life Cyclementioning
confidence: 99%